The Influence of Loan Capital and Acceptable Turnover on The Results of Operations in Employee Cooperatives PT. Tristex Independent - Nastiti Rizky Shiyammurti; Teni Kusherawati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The purpose of this study was to see the effect of loan capital and accounts receivable turnover on the remaining operating results of the cooperative employees of PT. Tristex Mandiri Cimahi. The population in this study is data on cooperative financial reports as many as 6 financial reports for 2015-2020. The sampling technique uses the census sampling method or saturated samples. The research design uses descriptive methods and associative methods. The analytical method uses multiple linear regression analysis. Based on the results of the study showed that partially there is no significant effect of loan capital variable on the remaining operating results , and partially there is a positive and significant effect of accounts receivable turnover on the remaining operating results . Simultaneously there is the effect of loan capital and accounts receivable turnover on the remaining operating results . Based on the value of R Square obtained by 0.908 or 90.8 %, this means that loan capital and accounts receivable turnover can affect the remaining operating results of 90.8 % , the remaining 90.8 % 9.2 % is influenced by other variables that are not involved in this study